EU Lessons on Digital Market Dominance for Indonesia and the Philippines - Lu Sudirman; Febri Jaya; Nur Fatihah; David Tan; Ninne Zahara Silviani (Greenation International Journal of Law and Social Sciences, 2026)
This study aims to examine the adequacy of antitrust frameworks in Indonesia and the Philippines in addressing digital market dominance, particularly when benchmarked against the European Union’s Digital Markets Act (DMA). This objective is aimed at addressing the literature gap where existing studies have yet to systematically assess how ex-ante regulatory logic, as pioneered in the EU context, can be normatively adapted to the specific deficiencies of Southeast Asian antitrust frameworks. The research employs a normative legal method combined with a comparative approach, analyzing statutory regulations and relevant legal literature, including Indonesia’s Law No. 5 of 1999, the Philippine Competition Act, and the EU DMA. The findings reveal that both countries’ competition laws are inadequate in addressing the complexities of digital markets, particularly in relation to data control, network effects, algorithmic practices, and platform dependency. Indonesia’s framework is significantly outdated, while the Philippines’ law, although more recent, still lacks digital-specific provisions. Aside from normative deficiency identification, the benchmarking against DMA also reveals that the ex-ante approach is more suitable to address today’s digital platform dynamic, which leads this study to contribute a legal development model for both Indonesia and the Philippines, each tailored to their existing normative architecture